The role of telemedicine in healthcare: an overview and update - Mason Stoltzfus; Arshdeep Kaur; Avantika Chawla; Vasu Gupta; F. N. U. Anamika; Rohit Jain (The Egyptian Journal of Internal Medicine, 2023)
Abstract Background First implemented in the 1950s, telemedicine is a rapidly evolving tool for healthcare systems around the world. Technological advancement and increasing access to information technology have made the implementation of telemedicine more feasible. Recent provisions by healthcare governing bodies have increased reimbursement for and the use of telemedicine globally. We have done a literature review to find out the pros and cons of adopting telemedicine. Main body Telemedicine is found to offer many benefits to conventional, in-person healthcare encounters for both patients and providers: decreased travel cost and time, decreased time spent in waiting rooms, decreased risk of transmission of communicable diseases, decreased overall encounter time consumption, increased convenience, and more. Telemedicine also facilitates seamless transitions of care between healthcare teams, connects isolated people groups with healthcare providers, and helps address regional healthcare infrastructure and provider shortages by connecting patients with healthcare teams from any location. Drawbacks specific to telemedicine include the lack of accessibility and advancement of imaging technology required to replace in-person physical examinations, nonuniversal access to the required devices and networks across the general patient population, and the risk of technical difficulties such as network connection disruptions. Conclusion Telemedicine helps bridging the gap of distance by connecting patients in remote locations with the physicians. This has also become vital in the time pandemic.